2022
DOI: 10.1038/s41598-022-05781-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of fall armyworm indicate a new introduction into Africa and identify limits to its migratory behavior

Abstract: The fall armyworm, Spodoptera frugiperda (J.E. Smith) is native to the Americas and a major pest of corn and several other crops of economic importance. The species has characteristics that make it of particular concern as an invasive pest, including broad host range, long-distance migration behavior, and a propensity for field-evolved pesticide resistance. The discovery of fall armyworm in western Africa in 2016 was followed by what was apparently a remarkably rapid spread throughout sub-Saharan Africa by 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…frugiperda (Nagoshi et al 2022), in populations from China (Jiang et al 2022), in Africa (e.g., Benin vs. Malawi; , and in, e.g., Australia, Malaysia, and Myanmar vs. China populations (Rane et al 2022),…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…frugiperda (Nagoshi et al 2022), in populations from China (Jiang et al 2022), in Africa (e.g., Benin vs. Malawi; , and in, e.g., Australia, Malaysia, and Myanmar vs. China populations (Rane et al 2022),…”
Section: Discussionmentioning
confidence: 99%
“…Novel introductions leading to unique population structure has been reported for western African S. frugiperda (Nagoshi et al 2022), in populations from China (Jiang et al 2022), in Africa (e.g., Benin vs. Malawi; Tay et al 2022a), and in, e.g., Australia, Malaysia, and Myanmar vs. China populations (Rane et al 2022), suggesting that the widely anticipated long distance migration of S. frugiperda especially in the invasive range could likely be less and may be impacted by localised ecological and climatic determinants (Tay et al 2022b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long distance migration enables FAW populations to travel from Southern Texas and Florida up to Canada, a distance of nearly 2500 km, in less than three months 11,35 . Therefore given its strong ight performance, we can hypothesize that FAW is also performing long distance migration within Brazil su cient to keep populations homogeneous within each host strain.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on molecular markers indicated that the invasive FAW originated from a single source with a high similarity to samples from Florida and the Greater Antilles (Nagoshi et al 2017;Nagoshi et al 2020), while other studies using genome-wide analyses supported multiple introductions of FAW into Africa and suggested South America as a potential source of FAW invasion into Africa (Nagoshi et al 2022;Tay et al 2022). In the Western hemisphere, the FAW has undergone a divergence into two "strains", a rice-strain and a corn-.…”
Section: Introductionmentioning
confidence: 99%